Introduction to Special Topic Forum: Where are the New Theories of Organization? - Suddaby, Roy; Hardy, Cynthia; Huy, Quy Nguyen (Academy of Management Review, 2011)
We summarize the manifest and latent content of the articles that make up the Special Topic Forum on Theory Development. Rather than offering new theories, however, most of the articles offer a series of critical accounts of current organizational theory and a range of novel ideas about the process of theory construction. We conclude by speculating about the institutional barriers to new theory creation and how those barriers might be changed.